Inhibition of AKT enhances chemotherapy efficacy and synergistically interacts with targeting of the Inhibitor of apoptosis proteins in oesophageal adenocarcinoma - Leanne Stevenson; Lauren Cairns; Xiaodun Li; Sriganesh Jammula; Harriet Taylor; Rosalie Douglas; Niamh McCabe; Gerald Gavory; Xavier Jacq; Rebecca C. Fitzgerald; Richard D. Kennedy; Timothy Harrison; et al. (Scientific Reports)
Abstract The incidence of oesophageal adenocarcinoma (OAC) has risen six-fold in western countries over the last forty years but survival rates have only marginally improved. Hyperactivation of the PI3K-AKT-mTOR pathway is a common occurrence in OAC, driving cell survival, proliferation and resistance to chemotherapeutic agents. Inhibition of AKT has been explored as a treatment strategy with limited success and current inhibitors have failed to progress through clinical trials. Our study, describes a novel allosteric AKT inhibitor, ALM301, and demonstrates an enhancement of the efficacy of conventional chemotherapy when combined with ALM301 in OAC. Reduced sensitivity to ALM301 is associated with high expression of the Inhibitor of Apoptosis (IAP) family of proteins, particularly XIAP. Combined AKT and IAP inhibition synergistically enhanced OAC cell death and successfully re-sensitized ALM301 and chemotherapy resistant cell lines. A high degree of synergism was also observed in patient-derived OAC organoids indicating the potential clinical relevance of the combination. This study demonstrates the role for dual AKT/IAP inhibition in OAC and provides a strong rationale for the further investigation of this highly efficacious combination strategy.